Frostbite and Mortality in Mountaineering Women: A Scoping Review-UIAA Medical Commission Recommendations - Kriemler, Susi; Mateikaitė-Pipirienė, Kastė; Rosier, Alison; Keyes, Linda E; Paal, Peter; Andjelkovic, Marija; Beidleman, Beth A; Derstine, Mia; Pichler Hefti, Jacqueline; Hillebrandt, David; Horakova, Lenka; Jean, Dominique (High altitude medicine & biology, 2023)
Kriemler, Susi, Kastė Mateikaitė-Pipirienė, Alison Rosier, Linda E. Keyes, Peter Paal, Marija Andjelkovic, Beth A. Beidleman, Mia Derstine, Jacqueline Pichler Hefti, David Hillebrandt, Lenka Horakova, and Dominique Jean; for the UIAA MedCom Writing Group on Women's Health in the Mountains. Frostbite and mortality in mountaineering women: a scoping review-UIAA Medical Commission recommendations. High Alt Med Biol. 24:247-258, 2023. Background: The harsh environment of high altitudes (HA) poses many serious health risks for mountaineers, including cold injuries and death. The aim of this work was to review whether female mountaineers are at special risk for frostbite or death at HA compared with their male counterparts. Methods: The UIAA Medical Commission convened an international author team to review women's health issues at HA and to publish updated recommendations. Pertinent literature from PubMed and Cochrane was identified with additional publications found by hand search. The primary search focus was for articles assessing cold injuries and death in women mountaineers at HA. Results: We reviewed the literature and identified 20 relevant studies: 2 studies on frostbite at HA, plus 7 studies and 1 report for death at HA. An additional 10 studies about frostbite at low altitude were included. We found that female mountaineers at HA were at lower risk of death than their male counterparts, but sex differences in frostbite were inconclusive. Conclusions: The frequency of cold injuries and mortality in female mountaineers is not yet well studied, and the studies that have been published tend to lack precise exposure data. More studies and registries with sex-differentiated data are needed.
Keywords: nadmořská výška; Registries; omrzliny; ruka; registrace; lidé; Female; mužské pohlaví; Altitude; Male; Mountaineering; Hand; Frostbite; ženské pohlaví; horolezectví; Humans